Preparation, characterization and evaluation of drug-delivery systems: Pectin and mefenamic acid films - Moreira, R. B.; Teixeira, J. A.; Furuyama-Lima, Aline Margarete [UNESP]; Souza, N. C. de; Siqueira, A. B. (Elsevier B.V., 2014)
Mefenamic acid (H-Mef) is a nonsteroidal anti-inflammatory drug (NSAID). Various adhesive dosage forms of NSAIDs have been developed, which include adhesive tablets, gels, ointments, patches and more recently, polymeric films. The objective of this study was the development of H-Mef adhesive films to be used as a drug-delivery system with different ratios of pectin and calcium chloride dihydrate by the casting technique. The materials were characterized by TG-DSC coupled FTIR, AFM (atomic force microscopy) and spectroscopic techniques. The results provided information about the dehydration, film roughness, surface morphology, thermal decomposition, as well as identification of gaseous products evolved during thermal decomposition. The characterizations indicated the A5 and A6 films functioned well, with 99% H-Mef released within 15 min at pH 5, suggesting these degradable films could be used as a topical delivery system. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Pectin; Mefenamic acid; Films; Thermal behaviour